1994
DOI: 10.1007/bf00176497
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged vital cartilage graft preservation using tissue culture methods

Abstract: Cartilage grafting is one of the most commonly performed procedures in plastic surgery. Since storage of both autologous and allogenic cartilage is necessary, different preservation methods have been used with varying success. The use of chemical preservation procedures such as formaldehyde, Merthiolate or Cialit lead to a loss of viability of the graft. This work presents a study of the cell viability of cartilage grafts stored in different solutions (saline, RPMI 1640 and DMEM) for 100 days. Cartilage immers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…13 In other studies, however, skin grafts stored under similar conditions lost approximately 90% of their viability after 10 days. 14,15 Therefore, there is a need to develop methods to maximize the viability of skin samples/grafts stored in refrigerators.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 In other studies, however, skin grafts stored under similar conditions lost approximately 90% of their viability after 10 days. 14,15 Therefore, there is a need to develop methods to maximize the viability of skin samples/grafts stored in refrigerators.…”
Section: Resultsmentioning
confidence: 99%
“…[23][24][25] Several authors have previously reported detailed histological changes in human skin grafts stored at 4 C in various configurations over a 4-week period. 1,2,8,[10][11][12][13][14][15] Cellular and nuclear swelling with pleomorphism have been reported to be early changes in stored grafts; nevertheless, grafts at this stage are believed to be viable. The formation of blebs that lead to epidermal separation is an important indicator of viable keratinocytes.…”
Section: Resultsmentioning
confidence: 99%